Angular-Based Mueller Matrix Polarimetry Parameters for Subwavelength Pore Size Differentiation - Wan, Jiachen; Wang, Chuhui; Wang, Chunnan; Sun, Shuqing; Ma, Hui (Frontiers in Physics, 2022)
Mueller Matrix polarimetry is exploited to find potential polarization feature sensitive to subwavelength pore sizes variation in Porous Alumina samples. After careful analysis using standard machine learning methods, it is observed that existing Mueller Matrix decomposition methods and parameters are insufficient to distinguish areas with different pore sizes. Thus, a new angular-based Mueller Matrix polarimetry parameter is proposed, capable of linearly separating areas with varying pore sizes. Such angular-based parameter is novel because it is based on angular parameters, it utilizes multi-angle measurements, and it extracts physical information independent from existing decomposition methods or parameters. Hopefully this work should inspire future research on the angular parameters in Muller Matrix Polarimetry and their relationships to microstructure information.